MAPPING THE LANDSCAPE OF DIGITAL INQUIRY-BASED LEARNING: A BIBLIOMETRIC ANALYSIS - Azneezal Ar-Rashid Mohd Ramli; Mohamad Termizi Borhan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This bibliometric analysis seeks to provide an in-depth examination of the academic landscape surrounding Digital Inquiry-Based Learning (DIBL). As digital technologies increasingly reshape educational practices, there is a pressing need for a comprehensive understanding of the research trends, key contributors, and thematic developments within this domain. The problem addressed by this study lies in the limited synthesis of the growing body of literature on DIBL, which hinders a nuanced understanding of its evolution and impact. To address this gap, we employed Scopus Analyzer and VOSviewer software to analyze a dataset comprising 1071 academic publications related to DIBL. The analysis identifies prevailing trends in publication volume, influential authors and institutions, and the key thematic clusters driving the field. Our findings indicate a marked increase in research output over recent years, with notable contributions from both the fields of educational technology and pedagogical research. The study further reveals distinct research clusters focused on the integration of digital tools into inquiry-based pedagogies, the effectiveness of such tools in enhancing student engagement, and their impact on learning outcomes. In conclusion, this bibliometric study provides a comprehensive mapping of the DIBL research landscape, offering critical insights into its current state and emerging directions. The findings contribute to a more informed understanding of how digital inquiry-based approaches are evolving and their implications for future educational practices.